Reflections of culture and comfort in a cup of coffee: Observing M. Aboe Talib coffee shop - Wajdi, Majid; Susanto, Budi; Sutiarso, M. Agus; Waelan, Waelan (Journal of Commerce, Management, and Tourism Studies, 2024)
This study was conducted to observe and evaluate Kedai Kopi M.Aboe Talib, a western Indonesian style of coffee stand that was located on the east part of Denpasar. This study applies observational method that observed at the coffee shop atmosphere, services and product provided. We conducted observations by recorded in-situ constraints and opportunities faced followed by customer interactions, interior design and coffee quality. The analysis results based on this research is that Kedai Kopi M. Aboe Talib succeeded in creating a comfortable and homey atmosphere by decorating the interior with local wisdom and traditions of Indonesians. Smiling customer service also contributes to a delighted client experience. The coffee products have a staple quality and level to of taste and fragrant that fulfil the expectations of the customers. So Kedai Kopi M. Aboe Talib whereas not solely serves as a spot, likes to sip coffee however has reworked into the social area units of services that may strengthen Indonesian cultural identity through design and also the services being offered. All told, the coffee shop is a net-positive for the culinary landscape of Burbank and an example of how coffee shops now more than ever can be at the centre of our social-cultural town life.